Journal of Cotton Research
The journal sets out to unite researchers conducting cotton research in agricultural, biological, bioengineering and material fields. Publications shall contribute to promote multidisciplinary development of cotton science and technology. Topics of interest include, but are not limited to: Germplasm resources & evolution, genetics & breeding Agricultural study: Agronomy, integrated pest management & bio-safety, weed science and agricultural engineering Biotechnology & bioengineering Bioinformatics Cotton molecular and cell biology, physiology and pathology Fiber process & inspection.